2014
DOI: 10.1016/j.conb.2014.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Central pattern generator for vocalization: is there a vertebrate morphotype?

Abstract: Animals that generate acoustic signals for social communication are faced with two essential tasks: generate a temporally precise signal and inform the auditory system about the occurrence of one’s own sonic signal. Recent studies of sound producing fishes delineate a hindbrain network comprised of anatomically distinct compartments coding equally distinct neurophysiological properties that allow an organism to meet these behavioral demands. A set of neural characters comprising a vocal-sonic central pattern g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 48 publications
0
31
0
Order By: Relevance
“…The current study maps FoxP2 mRNA expression in the brain of the highly vocal plainfin midshipman (Porichthys notatus) that has been the subject of comprehensive mapping of the central vocal, auditory, and neuroendocrine systems that modulate vocal-acoustic behaviors [ Fig. 1; see reviews in Bass, 2014;Forlano et al, 2015;Feng and Bass, 2017]. Comparison of the brain expression pattern of FoxP2 in midshipman with findings in other teleosts, as well as in mice and birds, suggests a pattern of evolutionarily conserved FoxP2-expressing brain regions.…”
Section: Introductionmentioning
confidence: 81%
“…The current study maps FoxP2 mRNA expression in the brain of the highly vocal plainfin midshipman (Porichthys notatus) that has been the subject of comprehensive mapping of the central vocal, auditory, and neuroendocrine systems that modulate vocal-acoustic behaviors [ Fig. 1; see reviews in Bass, 2014;Forlano et al, 2015;Feng and Bass, 2017]. Comparison of the brain expression pattern of FoxP2 in midshipman with findings in other teleosts, as well as in mice and birds, suggests a pattern of evolutionarily conserved FoxP2-expressing brain regions.…”
Section: Introductionmentioning
confidence: 81%
“…For instance, a recent study in rats revealed that expiratory laryngeal motor neurons in the nucleus ambiguus receive close appositions from descending TH-ir varicosities that originate, in part, from the AP and nucleus tractus solitarius [Zhao et al, 2015]. These caudal TH- ir groups also likely provide local innervation of the nucleus ambiguus in mammals [Rinaman, 2011], the tracheosyringeal division of the hypoglossal motor nucleus in birds [Bottjer, 1993; Mello et al, 1998; Appeltants et al, 2001], and the vagal motor nucleus and inferior reticular formation (Ri) in amphibians [Gonzalez and Smeets, 1991], all comparable vocal areas to midshipman VPG nuclei [Bass et al, 2008; Bass, 2014]. As a result, CA modulation of vocal motor patterning may also be a conserved vertebrate character [Forlano et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…Batrachoidid fishes (midshipman and toadfishes) possess a straightforward repertoire of vocalizations complemented by vocal circuitry that is evolutionarily conserved [Goodson and Bass, 2002; Bass et al, 2008; Bass, 2014]. The plainfin midshipman fish, Porichthys notatus , is a well-studied neuroethological model for investigating the neural and hormonal mechanisms underlying vertebrate vocal behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative analysis of development led to the hypothesis that an evolutionarily conserved neural network in the caudal medulla generates vocalization (Bass, 2014; Bass and Baker, 1997; Bass et al, 2008). Output from this conserved vocal generator projects to hindbrain and cervical spinal cord premotor and motor neurons leading to species-specific vocalization behaviors (Bass, 2014). Whether these premotor and motor neurons are also evolutionarily conserved is unclear.…”
Section: Introductionmentioning
confidence: 99%